Density, compressive strength, and impact of seawater on untreated timber-foamed concrete as a floating mechanism / Mizan Adillia Ahmad Fuad, Zalena Abdul Aziz and Nooriati Taib - Ahmad Fuad, Mizan Adillia; Abdul Aziz, Zalena; Taib, Nooriati Taib (Universiti Teknologi MARA, Perak, 2023)
Land shortages and rising sea levels are now being addressed by floating architecture. Studies on lightweight concrete as a suitable building material for structures on the water have been conducted. Therefore, this article focuses on the addition of untreated timber husk to lightweight concrete (foamed concrete) to diversify and sustainably produce construction materials. This study was designed to examine the durability and buoyancy of untreated timber husk as an addition to foamed concrete as a building material for floating architecture through an experimental approach fixed with numerical analyses on the specification and qualities of lightweight. The results of the quantitative method demonstrated that it was possible to build floating timber-foamed concrete using samples that range in density from 437.5 to 993.3 kg/m³. Each model's compressive strength was measured over a range of curing times, with TH05 producing the highest readings of 2.27 MPa and 0.89 MPa after submerging in seawater. The impact rate from saltwater towards the strength was highest at TH10 with only a 0.25 MPa difference, and the surface of each concrete showed the most reaction on TH15, which was also used to analyse the buoyancy of samples over time. To determine the effects of seawater overtime on the density and strength of timber-foamed concrete, further analysis of seawater's influence shall be conducted to enhance the materiality of floating architecture.